Using Social Media to Help Students Obtain Success Scripts for Job, Career, and Life Achievement - Palmbach, Shanon; Zubell, Carly (My University, 2012)
Using social media and qualitative software techniques, this study proposed to identify key job, career, and life success scripts from UW-Eau Claire Marketing alumni.
Color poster with text, tables, and graphs.
Keywords: Social media; Curriculum planning; Job hunting; Vocational guidance; Life skills; Posters